Assuring food and nutrition security in Africa by 2020 -- prioritizing actions, strengthening actors, and facilitating partnerships: proceedings of all-Africa conference - International Food Policy Research Institute (International Food Policy Research Institute, 2004)
Africa may at last be poised to make real progress on achieving food and nutrition security. Although the number of Africans who are undernourished has been on the rise for decades and now stands at about 200 million, a new commitment to change has emerged both among African leaders and in the international community. The seeds for the 2020 Africa Conference documented in this volume were planted on September 4–6, 2001, when the International Food Policy Research Institute’s (IFPRI’s) 2020 Vision for Food, Agriculture, and the Environment Initiative held an international conference on “Sustainable Food Security for All by 2020” in Bonn, Germany. A wide variety of stakeholders—more than 900 from over 70 countries—came together to examine how to cope with emerging developments, assess progress in alleviating food insecurity, and forge a consensus on how best to realign local and global priorities for eliminating hunger. During and after that conference, African partners, arguing that hunger and malnutrition remain Africa’s most fundamental challenges, repeatedly urged IFPRI to organize a similar multistakeholder, multisector forum focused on how to bring about change and action to assure food and nutrition security in Africa.